2013
DOI: 10.1074/jbc.m112.437095
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Proteins Regulate Activation-induced Proteasomal Degradation of the Mature Phosphorylated Form of Protein Kinase C

Abstract: Background: Mechanisms of activation-induced PKC down-regulation are poorly understood. A characterized pathway involves priming site dephosphorylation and degradation of the dephosphorylated species. Results: Mature, fully phosphorylated PKC␣ is a major target for activation-induced degradation, via mechanisms controlled by Hsps. Conclusion: Hsps control phosphorylation and degradation of fully primed, activated PKC. Significance: Findings from this study support a new model of PKC desensitization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 89 publications
(76 reference statements)
0
28
1
1
Order By: Relevance
“…Detailed analysis of this organelle have revealed it to serve as an intracellular hub for the accumulation of internalized cell surface receptors prior to their redirection to other destinations such as recycling back to cell surface or targeting to the lysosome. Indeed, the down-regulation of PKC-␣ upon its sustained activation with bryostatin or PMA has also been linked to endosome-lysosome traffic (109) and this effect is enhanced by 17-AAG (110). Biochemical characterization of the pericentrion/ERC compartment revealed that it contains a number of cell surface receptors including EGFR (67).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed analysis of this organelle have revealed it to serve as an intracellular hub for the accumulation of internalized cell surface receptors prior to their redirection to other destinations such as recycling back to cell surface or targeting to the lysosome. Indeed, the down-regulation of PKC-␣ upon its sustained activation with bryostatin or PMA has also been linked to endosome-lysosome traffic (109) and this effect is enhanced by 17-AAG (110). Biochemical characterization of the pericentrion/ERC compartment revealed that it contains a number of cell surface receptors including EGFR (67).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic DiC 8 Stimulation Does Not Result in Down-regulation of PKC␣-The ability of DiC 8 to support sustained activation of PKC␣ was surprising because it is well established that prolonged stimulation of PKC isozymes can lead to long term desensitization via degradation of the activated kinase (19,21,22). This down-regulation can be readily seen in PMA-and bryostatin-treated IEC-18 cells: as shown in Fig.…”
Section: Activation and Reversementioning
confidence: 84%
“…Two mechanisms have been described for agonist-induced ubiquitination/proteasomal degradation of PKC␣ (19,21,23). One pathway involves activation-dependent priming site dephosphorylation, which both inactivates the kinase and targets it for ubiquitin-dependent proteasomal degradation (9,19).…”
Section: Activation and Reversementioning
confidence: 99%
See 2 more Smart Citations